2015
DOI: 10.1002/trtr.1360
|View full text |Cite
|
Sign up to set email alerts
|

“How Do You Draw Freedom?”

Abstract: Art can be a powerful tool for making meaning. These authors describe what happened when students were challenged to draw a picture symbolizing the meaning of a story.Christine H. Leland is a professor in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…C made the following suggestions regarding incorporating a student-authored OER book project in teacher education classes. First, as she compared the students' weekly personal and their final open book, C found that although students used graphs and other visual images in the book, many artistic expressions, music, and other forms of "transmediation" (Leland et al, 2015) and multimodality demonstrated in their personal blog postings were unfortunately not included in the book. C also noticed that some good thinking and critical perspectives demonstrated in the students' personal blogs were not incorporated into the final publication.…”
Section: Implications and Reflectionsmentioning
confidence: 99%
“…C made the following suggestions regarding incorporating a student-authored OER book project in teacher education classes. First, as she compared the students' weekly personal and their final open book, C found that although students used graphs and other visual images in the book, many artistic expressions, music, and other forms of "transmediation" (Leland et al, 2015) and multimodality demonstrated in their personal blog postings were unfortunately not included in the book. C also noticed that some good thinking and critical perspectives demonstrated in the students' personal blogs were not incorporated into the final publication.…”
Section: Implications and Reflectionsmentioning
confidence: 99%